Aterosclerose coronária em indivíduos assintomáticos com deficiência do hormônio do crescimento - Burgos, Ursula Maria Moreira Costa (2016)
GH and its principal mediator IGF-I have important effects on metabolic and cardiovascular (CV) status. While acquired GH deficiency (GHD) is often associated to increased CV risk, the consequences of congenital GHD are not known. We have described a large group of patients with isolated GHD (IGHD) due to a homozygous mutation (c.57+1G>A) in the GH releasing hormone receptor gene, and shown that adult GH-naïve individuals have no evidence of clinically evident premature atherosclerosis. To test weather subclinical atherosclerosis is anticipated in untreated IGHD, we ruled a cross-sectional study of 25 IGHD and27 adult controls matched for age and gender. A comprehensive clinical and biochemical panel and coronary artery calcium scores by multi-detector tomography were evaluated. Height, weight, IGF-I, homeostasis model assessment of insulin resistance, creatinine and creatinokinase were lower in IGHD group. Median and interquartile range of calcium scores distribution was similar in the two groups: IGHD 0 (0) and control 0 (4.9). The vast majority of the calcium scores [20 of 25 IGHD (80%) and 18 of 27 controls (66.6%)] were equal to zero (difference not significant). There was no difference in the calcium scores classification. None of IGHD subjects had minimal calcification, which were present in 4 controls. Three IGHD and four controls had mild calcification. There were two IGHD individuals with moderate calcification and one control with severe calcification. Our study provides evidence that subjects with congenital isolated lifetime and untreated severe IGHD do not have accelerated subclinical coronary atherosclerosis.